IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER (PPK) PADA SISWA SD MUHAMMADIYAH 29 SURABAYA KELAS II DI ERA PANDEMI COVID-19 - Miko Fitri Ana; Badruli Martati; Kunti Dian Afiani (Universitas Negeri Medan, 2022)
Abstract : Implementation of Strengthening Character Education for The Second Grade Students of Muhammadiyah 29 Surabaya Elementary School In the Era of the Covid-19 Pandemic. The impact of the COVID-19 pandemic that hit Indonesia caused the learning system to be changed remotely to